PENGARUH FAKTOR PSIKOLOGIS TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN PADA WISATA RELIGI GUNUNG KAWI MALANG (Studi Pada Pengunjung Wisata Religi Gunung Kawi Malang) - Yunikasari, Hefriza Nurma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research to analyze the influence of psychological factors which consist of motivation, perception, learning, beliefs, and attitudes on the decision travelers visiting Gunung Kawi religious tourism Malang City (studies on a visitor Gunung Kawi religious tourism Malang City). This research using explanatory research and the sample was 100 respondents. Sampling was carried out with non-probability sampling method using purposive sampling. Test equipment used to test the research instruments such as validity test, reliability test and test the classical assumption of normality test, multicolinearity test and heteroscedasticity test. For data analysis techniques using multiple linear regression analysis. Hypothesis testing using F test, t test, and dominant test.The results showed that the motivation, perception, learning, beliefs, and attitudes has an effect simultaneously toward the decision travelers visiting Gunung Kawi religious tourism Malang City. The analysis also showed that partial each variable, only perception, learning, beliefs, and attitudes has a significantly influence, while motivation did not significantly affect with beliefs as variable that has dominant influence toward the decision travelers visiting Gunung Kawi religious tourism Malang City.Keywords: Psychological Factors, Motivation, Perception, Learning, Beliefs, and Attitude, Decision to Visit, Gunung Kawi Relious Tourism Malang City